PENGGUNAAN MEDIA PEMBELAJARAN PODCAST UNTUK MENINGKATKAN KETERAMPILAN MENULIS PESERTA DIDIK KELAS V SEKOLAH DASAR - Adlini, Lissa; Ramadhan, Syahrul; Sukma, Elfia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The writing skills of fifth grade students at SDN Percobaan Kota Padang are still low. Most students in pouring stories into writing are a little overwhelmed in finding ideas. In addition, there is a lack of use of learning media in the classroom. This certainly makes the learning process hampered so that students cannot develop their ideas in writing. The purpose of this study in general is to test the use of podcast learning media to improve the writing skills of grade V students of SDN Percobaan Kota Padang. This study used a One-Group Pretest-Posttest experimental design. Data was collected from teacher and student activities. There were also tests related to the data collection method.